Molecular imaging reveals elevated VEGFR‐2 expression in retinal capillaries in diabetes: a novel biomarker for early diagnosis. Issue 9 (5th June 2014) - Sun, Dawei; Nakao, Shintaro; Xie, Fang; Zandi, Souska; Bagheri, Abouzar; Kanavi, Mozhgan Rezaei; Samiei, Shahram; Soheili, Zahra‐Soheila; Frimmel, Sonja; Zhang, Zhongyu; Ablonczy, Zsolt; Ahmadieh, Hamid; et al.
Abstract : Diabetic retinopathy (DR) is a microvascular complication of diabetes and a leading cause of vision loss. Biomarkers and methods for early diagnosis of DR are urgently needed. Using a new molecular imaging approach, we show up to 94% higher accumulation of custom designed imaging probes against vascular endothelial growth factor receptor 2 (VEGFR‐2) in retinal and choroidal vessels of diabetic animals ( P <0.01), compared to normal controls. More than 80% of the VEGFR‐2 in the diabetic retina was in the capillaries, compared to 47% in normal controls ( P <0.01). Angiography in rabbit retinas revealed microvascular capillaries to be the location for VEGF‐A‐induced leakage, as expressed by significantly higher rate of fluorophore spreading with VEGF‐A injection when compared to vehicle control (26±2 vs. 3±1 μM/s, P <0.05). Immunohistochemistry showed VEGFR‐2 expression in capillaries of diabetic animals but not in normal controls. Macular vessels from diabetic patients ( n =7) showed significantly more VEGFR‐2 compared to nondiabetic controls ( n =5) or peripheral retinal regions of the same retinas ( P <0.01 in both cases). Here we introduce a new approach for early diagnosis of DR and VEGFR‐2 as a molecular marker. VEGFR‐2 could become a key diagnostic target, one that might help to prevent retinal vascular leakage and proliferation in diabetic patients.—Sun, D., Nakao, S., Xie, F., Zandi, S., Bagheri, A., Kanavi, M. R., Samiei, S., Soheili, Z.‐S., Frimmel, S., Zhang, Z., Ablonczy, Z., Ahmadieh, H., Hafezi‐Moghadam, A. Molecular imaging reveals elevated VEGFR‐2 expression in retinal capillaries in diabetes: a novel biomarker for early diagnosis. FASEB J. 28, 3942‐3951 (2014). www.fasebj.org